Synergistic and antagonistic pleiotropy of STOP1 in stress tolerance. (October 2021) - Sadhukhan, Ayan; Kobayashi, Yuriko; Iuchi, Satoshi; Koyama, Hiroyuki
Abstract : SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) is a master transcription factor (TF) that regulates genes encoding proteins critical for cellular pH homeostasis. STOP1 also causes pleiotropic effects in both roots and shoots associated with various stress tolerances. STOP1-regulated genes in roots synergistically confer tolerance to coexisting stress factors in acid soil, and root-architecture remodeling for superior phosphorus acquisition. Additionally, STOP1 confers salt tolerance to roots under low-potassium conditions. By contrast, STOP1 antagonistically functions in shoots to promote hypoxia tolerance but to suppress drought tolerance. In this review, we discuss how these synergetic- and antagonistic-pleiotropic effects indicate that STOP1 is a central hub of stress regulation and that the harmonization of STOP1-regulated traits is essential for plant adaptation to various environments. Highlights: The zinc-finger transcription factor STOP1 regulates various stress-tolerance genes in arabidopsis. In roots, STOP1 regulates Al 3+ and H + tolerances, as well as root remodeling under phosphorous-deficient conditions, and this synergistically improves tolerance to acid soil syndrome. In shoots, STOP1 confers hypoxia tolerance by regulating the cytosolic pH, but it suppresses drought tolerance by regulating K + transport. A major target of STOP1 in roots, ALMT1, is a key protein controlling its pleiotropic effects, including acid soil-, alkaline-, and biotic stress-tolerance levels.